1991
DOI: 10.1111/j.1651-2227.1991.tb11828.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Dose Intravenous Gammaglobulin Therapy for Neonatal Immune Haemolytic Jaundice due to Blood Group Incompatibility

Abstract: Three newborn infants who developed hyperbilirubinemia due to blood group incompatibility were treated with high-dose gammaglobulin. Hyperbilirubinemia was caused by Rhesus (Rh) incompatibility (anti-E + anti-c) in Infant 1 and ABO incompatibility (anti-B) in Infants 2 and 3. Hyperbilirubinemia was refractory to conventional phototherapy but responded well to intravenous gammaglobulin (IVGG) at a dose of 1 g/kg in all infants. No adverse effects were observed. These findings suggest that high-dose IVGG may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 14 publications
1
35
0
1
Order By: Relevance
“…[61][62][63] The rationale behind this indication is that in isoimmune hemolytic disease, hyperbilirubinemia results primarily from erythrocyte phagocytosis in the reticuloendothelial system. 64 The administration of endovenous gammaglobulin would block Fc receptors from the reticuloendothelial system, decreasing the speed of hemolysis.…”
Section: Endovenous Gammaglobulinmentioning
confidence: 99%
See 1 more Smart Citation
“…[61][62][63] The rationale behind this indication is that in isoimmune hemolytic disease, hyperbilirubinemia results primarily from erythrocyte phagocytosis in the reticuloendothelial system. 64 The administration of endovenous gammaglobulin would block Fc receptors from the reticuloendothelial system, decreasing the speed of hemolysis.…”
Section: Endovenous Gammaglobulinmentioning
confidence: 99%
“…62 The dose and interval of immunoglobulin administration varies from 0.5g to 1g. [61][62][63][64][65] Alpay et al treated 116 newborns with ABO and/or Rh hemolytic disease with 1g endovenous immunoglobulin (single dose). These patients required less phototherapy and fewer exchange transfusions, and spent less time in the hospital.…”
Section: Endovenous Gammaglobulinmentioning
confidence: 99%
“…Recent studies [1][2][3] have demonstrated that intravenous immune globulin (IVIG) therapy is effective in modifying the hyper bilirubinemia of Coombs'-positive hemolytic anemia. While IVIG clearly reduces hyper bilirubinemia in many cases of neonatal iso immunization, it is not always successful [2], We therefore sought to elucidate the type of infant most likely to benefit from IVIG ad ministration by attempting to define pretreat ment parameters which were associated with both clinical symptomatology and therapeutic responsiveness to IVIG.…”
mentioning
confidence: 99%
“…It has been suggested that the administration of im munoglobulin in neonatal immune hyperbilirubinemia may reduce hemolysis by blockade of the Fc receptors [1][2][3]. Flowever, despite the reported reduction of bilirubin levels following IVIG treatment, the existence of such a mecha nism has not yet been proved and other explanations for the observed effect, such as enhanced excretion of bilirubin or colloid effects, remain to be examined [3].…”
Section: Introductionmentioning
confidence: 99%
“…The catabolism of heme, derived mainly from the degra dation of hemoglobin, is the sole endogenous source of carIn recent years several reports have indicated that the se verity of neonatal immune hemolytic hyperbilirubinemia may be ameliorated by the intravenous administration of high-dose immunoglobulin (IVIG), thus reducing the need for exchange transfusion [1][2][3][4], The rationale for this treat ment was based on the assumed similarity between the de structive mechanisms of antibody-sensitized erythrocytes in immune hemolytic jaundice and of antibody-sensitized platelets in neonatal immune thrombocytopenia [3,5,6], and on the beneficial therapeutic effect of high-dose IVIG treatment reported in the latter disease [7][8][9]. bon monoxide.…”
Section: Introductionmentioning
confidence: 99%